THE ROLE OF SEO IN STRENGTHENING DIGITAL MARKETING STRATEGY TO BOOST SMES COMPETITIVENESS IN THE ORGANIC MARKET - Irfan Ardiansah; Yanti Rubiyanti; Josua Pandaoni (KOMPLEKSITAS: JURNAL ILMIAH MANAJEMEN, ORGANISASI DAN BISNIS, 2025)
This study investigates the strategic application of Search Engine Optimization (SEO) as a digital marketing tool for small and medium-sized enterprises (SMEs), focusing on an organic products business transitioning to e-commerce. Utilizing a mixed-methods framework, the study assesses the effectiveness of SEO methodologies. Results reveal that optimizing product titles, descriptions, and metadata improved search engine rankings, increasing organic traffic by 28% over three months. However, the conversion rate saw only a marginal rise (from 1.78% to 2.15%), underscoring gaps in user experience and technical SEO implementation. The study also highlights resource constraints and knowledge barriers that hinder SMEs from sustaining SEO efforts independently. These findings align with recent industry trends emphasizing the integration of SEO with content marketing and mobile optimization to address consumer behaviors. This research provides actionable recommendations for SMEs to harness SEO as a strategy for digital growth. The outcomes contribute to broader discourse on digital equity for SMEs in competitive markets, advocating for tailored training programs and collaborative platforms to democratize access to SEO tools.Penelitian ini bertujuan untuk penerapan strategis Search Engine Optimization (SEO) sebagai alat pemasaran digital untuk usaha kecil dan menengah (UKM), dengan fokus pada bisnis produk organik yang bertransisi ke e-commerce. Menggunakan kerangka kerja mixed-methods, studi ini menilai efektivitas metodologi SEO. Hasil penelitian menunjukkan bahwa pengoptimalan judul produk, deskripsi, dan metadata meningkatkan peringkat mesin pencari dan meningkatkan lalu lintas organik sebesar 28% selama tiga bulan. Namun, tingkat konversi hanya mengalami peningkatan marginal (dari 1,78% menjadi 2,15%), yang menggarisbawahi kesenjangan dalam pengalaman pengguna dan implementasi SEO teknis. Studi ini juga menyoroti kendala sumber daya dan hambatan pengetahuan yang menghalangi UKM untuk mempertahankan upaya SEO secara mandiri. Temuan ini sejalan dengan tren industri terkini yang menekankan integrasi SEO dengan pemasaran konten dan pengoptimalan seluler untuk mengatasi perilaku konsumen. Penelitian ini memberikan rekomendasi yang dapat ditindaklanjuti bagi UKM untuk memanfaatkan SEO sebagai strategi pertumbuhan digital. Hasil penelitian ini berkontribusi pada wacana yang lebih luas tentang kesetaraan digital bagi UKM di pasar yang kompetitif, dengan mengadvokasi program pelatihan yang disesuaikan dan platform kolaboratif untuk mendemokratisasi akses ke teknologi SEO